2009
DOI: 10.4103/0253-7613.59921
|View full text |Cite
|
Sign up to set email alerts
|

Adaptogenic effect of Morus alba on chronic footshock-induced stress in rats

Abstract: Objective:The objective of the present study was to evaluate the adaptogenic property of the ethyl acetate-soluble fraction of methanol extract of Morus alba roots against a rat model of chronic stress (CS).Materials and Methods:Rats were exposed to stress procedure for 21 days. The stress procedure was mild, unpredictable footshock, administered for 1 h once daily for 21 days. Rats were administered with the ethyl acetate soluble fraction of methanol extract of M. alba roots (25, 50 and 100 mg/kg p.o) 1 h bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 13 publications
(19 reference statements)
3
25
0
Order By: Relevance
“…Indeed, recent evidence links the stress-induced increases in glucocorticoids with dysregulation of glucose control (Gregoire et al 1991;Ahn et al 2016). Corticosterone mobilizes stored energy reserves in body tissues, leading to an elevated blood glucose levels (Nade et al 2009). Our lab has also previously shown that the underlying mechanism by which physical stress disrupt glucose control may involve blunting of insulin signaling in skeletal muscles (Morakinyo et al 2016).…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, recent evidence links the stress-induced increases in glucocorticoids with dysregulation of glucose control (Gregoire et al 1991;Ahn et al 2016). Corticosterone mobilizes stored energy reserves in body tissues, leading to an elevated blood glucose levels (Nade et al 2009). Our lab has also previously shown that the underlying mechanism by which physical stress disrupt glucose control may involve blunting of insulin signaling in skeletal muscles (Morakinyo et al 2016).…”
Section: Discussionmentioning
confidence: 97%
“…Under negative mode, neutral cleavages of H 2 O and CO 2 groups are the characteristic behaviors of stilbenes, and another neutral loss of a glycosyl group could be detected for stilbene glycoside. As the di-glycosidation product of oxyresveratrol, mulberroside A (3) was detected at the retention time (t R ) of 8.7 min by comparison with the reference compound, while oxyresveratrol (16) was observed at 14.7 min (Table 1 and Fig. 9).…”
Section: Characterization Of the Chemical Constituents In The MC Extractmentioning
confidence: 99%
“…Mulberry belongs to the Moraceae family, which includes 37 genera and over 1100 species [1] and has long been used as a traditional medicine and food in Korea, China, and Japan [2][3][4]. Mulberries are reported to exhibit numerous pharmacological activities, such as antidiabetic [5], antioxidant [6], anticancer [7], antistress [8], immunomodulatory [9], and hepatoprotective [10] activities. erefore, mulberries should be considered as important potential sources of bioactive compounds that can be used for the prevention or treatment of many di erent medical conditions.…”
Section: Introductionmentioning
confidence: 99%